The recent tectonic stress field of the Amur region - D. A. Safonov (Геодинамика и тектонофизика, 2018)
The Amur region (Priamurie) is located in the NE part of the Amur lithospheric plate and its surrounding territories. Seismic activity is moderate in Priamurie, and the regional earthquakes, including the strongest ones, occur mainly in three seismic belts: Stanovoi (the zone of influence of the eastern flank of the Stanovoi fault), Yankan-Tukuringra-Soktakhan (the eastern flank of the Mongolia-Okhotsk lineament), and Turan-Selemzhinsky (from the Lesser Khingan to the north). The Sakhalin Branch of FRC GS RAS Catalogue of focal mechanisms of 57 regional earthquakes provide the data for a more precise estimation of the parameters of the crustal stress state in the study area. The Cataclastic Analysis Method (CAM) developed by Yu.L. Rebetsky (stage 1) was used to estimate the orientations of the main axes of the stress tensor and the Lode – Nadai coefficient. The analysis shows that the Upper Priamurie is dominated by shearing and compression with shearing. The Amur plate moves relative to the Aldan-Stanovoi block along the South Tukuringra and North Tukuringa faults to the east. Vertical shearing is predominant along the Dzheltulak fault and the western segment of the North Tukuringra fault. The NNE-trending compression takes place in the area located east of the quiescence zone of the Dzhagda ridge. Along the Mongolia-Okhotsk fault system, near the Sea of Okhotsk, the direction of compression changes to the northward one. The tectonic stress field along the Tanlu fault zone is inhomogeneous and comprises the alternating zones of horizontal compression and stretching with varying directions of the main stress axes. To the east of the band characterized by the maximum seismic activity, compression changes its direction to the southeast- and eastward. Probably, the impact of the oceanic subduction on the northern part of the Japan-Korean block begins to manifest itself in this part of the Amur region. The tectonic stress field reconstructed from the seismological data is consistent with the measurements of the modern crustal movements. The results of our study can prove useful for clarifying the tectonics of the region.